Minding the gap: health and social care provider perceptions of parental communication and Black-Canadian youths' sexual health. Issue 12 (2nd December 2018) - Lee-Foon, Nakia; George, Clemon; Gahagan, Jacqueline; Etowa, Josephine; Weaver, Robert
Abstract: Health and social care providers' perceptions of Black-Canadian parent-youth sexual health communication has important implications for addressing knowledge gaps in the provision of services to young people and their parents. Providers' perceptions are crucial as they often act as advisers in tailoring programmes or services to the perceived needs of parents and youth. To understand these perceptions, 17 semi-structured in-depth interviews were conducted with providers who worked with African, Caribbean or Black (ACB) parents and youth in Toronto, Ontario, Canada. Critical Race Theory was used to help guide the interpretation of findings. The findings revealed providers believed that many parents were unlikely to explicitly discuss sexual health or HIV prevention with young people. Additionally, providers perceived that the content of and approach to parent-youth sexual health communication differed between African and Caribbean clients. Moreover, providers believed that both parents' and young people's sex and gender impacted the quality, content and style of sexual health communication and had important implications for programme development. Overall, findings suggest a need for understanding the development of providers' perceptions of this communication, ways to address these perceptions and further parent-provider collaboration to promote Black youths' sexual health.